Lessons learnt from the COVID-19 pandemic: results of EAHP survey on the future crisis preparedness of hospital pharmacies. Issue 5 (8th September 2021) - Leonardi Vinci, Daniele; Polidori, Piera; Miljković, Nenad; Batista, Aida; Amann, Steffen; Makridaki, Despina; Kohl, Stephanie
Abstract : Aim: The present survey aimed to collect information on the lessons learnt from the COVID-19 pandemic by hospital pharmacists. It focused on the shortages of health goods and the experiences of hospitals during the first phase of the crisis. Methods: A 17-question survey was conducted by EAHP, looking at the experiences of hospital pharmacists during the COVD-19 pandemic. The survey ran from 16 September to 23 December 2020. Statistical analysis included backward stepwise logistic regression (BSLR), Pearson's χ 2 test, t-test and one-way ANOVA, as appropriate; p≤0.05 was considered statistically significant. Results: 1466 hospital pharmacists answered the survey fully. 58%, 63% and 69% of them experienced shortages in medicines, disinfectants and personal protective equipment (PPE), respectively. BSLR showed that being a COVID-19 dedicated hospital increased the risk of medicine shortages (OR 1.63, 95% CI 1.15 to 2.31) but the shortages of disinfectants and PPE were lower (OR 0.62, 95% CI 0.44 to 0.88; OR 0.60, 95% CI 0.42 to 0.85). Being a specialised hospital reduced the odds of medicine shortages (OR 0.59, 95% CI 0.40 to 0.88), while countries with a greater percentage of the population infected had increased odds for all three types of shortages (OR 1.16, 95% CI 1.01 to 1.23; OR 1.34, 95% CI 1.19 to 1.50; OR 1.21, 95% CI 1.09 to 1.35). The odds were also higher in answers submitted in September compared with December. The classes of medicines with highest reported shortages were anaesthetics, antibiotics and muscle relaxants. The main entities that provided support were the national competent authorities and manufacturers. Conclusion: Medicine shortages affected the work of hospital pharmacists during the early stages of the pandemic. The features of the crisis and the feedback described in this survey can provide interesting insights for a more resilient healthcare framework in the future.